Nômos e epistéme: o problema da natureza da lei no Político de Platão - Richard Romeiro Oliveira (2000)
The idea of law shows a curious ambiguity in Plato's political thought; in the Republic and in several passages of the Politicus, it is strongly refused, and the best regime is said to be the imperium legihus soluíum of reason; in Laws, however, the largest work of corpus plalonicm, it is recovered and becomes the basis of the whole civil life. By taking the Politicus as our main focus of analisys, we will try to make out in the present text the meaning of this ambiguity and to demonstrate that the concept of sovereignty of law that overcomes the Plato's later political thought does not mean a denial of the intelectualistic ideal of the rule of reason, but only the way by wich this rule might take place in the history.